Making use of Digital Image Correlation to identify the true character of the applied load - Styk, Adam; Świder, Stanisław; Semenov, Sergei (Photonics Letters of Poland, 2023)
Digital Image Correlation became one of the dominant optical full-field techniques used in experimental mechanics. It does not require sophisticated equipment to evaluate the full displacement vector field of the specimen under test with great accuracy. In this paper, we would like to put the reader’s attention to the DIC technique as a solution that may identify the genuine character of the load applied to the object under test. Our experience with testing wind turbine blades using DIC proves that possibility. Full Text: PDF References E.M.C Jones, M.A. Iadicola, "A good practises guide for digital image correlation" International Digital Image Correlation Society, (2018), CrossRef B. Pan, "Digital image correlation for surface deformation measurement: historical developments, recent advances and future goals", Meas. Sci. Technol. 29, 082001 (2018), CrossRef B. Pan, L.P. Yu, Q.B. Zhang, "Review of single-camera stereo-digital image correlation techniques for full-field 3D shape and deformation measurement", Sci. China Technol. Sci. 61, 2 (2018), CrossRef S. Sharma, N. Iniyan Thiruselvam, S.J. Subramanian, G.S. Kumar, "Computation of strains from stereo digital image correlation using principal component analysis", Meas. Sci. Technol. 32, 105201 (2021), CrossRef IEC 61400-5:2020 Wind energy generation systems - Part 5: Wind turbine, DirectLink IEC 61400-23:2014 Wind turbines - Part 23: Full-scale structural testing of rotor blades, DirectLink